1978
DOI: 10.1063/1.325461
|View full text |Cite
|
Sign up to set email alerts
|

Thermoluminescence of LiF TLD-100: Glow-curve kinetics

Abstract: The thermoluminescence kinetics have been determined for the 13 glow peaks contained in the glow curves obtained from LiF TLD-100 after exposure to 60Co irradiations. The glow curves were constructed from measurements made with recently developed equipment for recording emission spectra at closely spaced temperature intervals. In addition, the recorded data has been subjected to all corrections needed to make it suitable for reliable kinetic analysis. The recorded emission spectra can be described by a single … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1980
1980
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Thereby, at low dose levels and under the usual annealing procedures, the interference from peak 4 accounts the greater problem. On the other hand, the existence of peak 5a was originally introduced by Fairchild et al [33], as a requirement to obtain a good fit to the experimental glow-curve of TLD . However, Gartia and Sing [34] and Abd El-Hafez et al [3] ignored this glow-peak in their analysis procedures.…”
Section: The Glow-curve Analysis Under Usual Thermal Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereby, at low dose levels and under the usual annealing procedures, the interference from peak 4 accounts the greater problem. On the other hand, the existence of peak 5a was originally introduced by Fairchild et al [33], as a requirement to obtain a good fit to the experimental glow-curve of TLD . However, Gartia and Sing [34] and Abd El-Hafez et al [3] ignored this glow-peak in their analysis procedures.…”
Section: The Glow-curve Analysis Under Usual Thermal Treatmentsmentioning
confidence: 99%
“…These peaks were referred as peaks 5a and 6. Peak 5a was originally introduced by Fairchild et al [33]. Kitis and Otto [36] concluded that this peak cannot seen in the usual glow-curve, resulting after the normal annealing.…”
Section: Introduction Harshaw Lif : Mgtimentioning
confidence: 99%
“…The model described with two energy levels is the simplest model that can be used to explain thermoluminescence but obviously is not sufficient to describe thermoluminescence from a real TL material at least because it cannot predict the presence of the several TL peaks in the material glow curve observed in the most popular TLDs, an instance being LiF with four glow peaks. Experimental observations have suggested the existence of a range of trapping and recombination [24], [25] as can be seen schematically in Fig. 2 above.…”
Section: Thermoluminescence and Optically Stimulated Luminescencementioning
confidence: 89%
“…The last parameter to be obtained is the relative value of n o (cm −3 ). Usually, n o is not evaluated by using one of the analytical methods, but instead, n o is taken either to be proportional to I m or proportional to the area under the peak, [1,18,26,27]. However, instead of using the peak height or peak area, an analytical method has been developed to obtain the relative value of n o in case of general-order glow peak, by inserting equation (16) into equation (6).…”
Section: Determination Of the Trap Parametersmentioning
confidence: 98%